Znaleziska z miejscowości Górzec w pow. strzelińskim w kontekście przemian kulturowych okresu wędrówek ludów - Gralak, Tomasz (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2017)
In the eighteenth and nineteenth century in the vicinity of the village of Górzec was found a set of artefacts probably representing scattered treasure from the beginning of the Migration Period. Such deposits are an expression of the rapid changes in the circulation of capital and the perception of value in this period. The influx of large quantities of gold and changes in silver’s value resulted in rapid changes in the status of various groups and individuals. An unstable social hierarchy is a prerequisite for the existence of the phenomenon of the potlatch, i.e. the ostentatious consumption or removal of goods from circulation. It seems that the deposits of the Migration Period should be considered this way. In 2010-2011 in the area of Górzec, excavations were undertaken. The aim was to discover of the remains of settlements from the time of the deposition of the treasure. As a result of this work, the existence of a settlement from phase D-D2 of the Migration Period was revealed. Hence, it is most likely that it is slightly younger than the treasure, but this is still open to question.